2021
DOI: 10.1007/s43545-021-00203-9
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the actions of Ibero-American universities to achieve social responsibility by promoting responsible competences

Abstract: The importance of Higher Education Institutions (HEI) for social development is unquestionable due to their potential to contribute with intellectual solutions to social, economic, and environmental welfare in society. However, the lack of knowledge about University Social Responsibility (USR) causes inefficient managerial decisions when strategies are implemented in areas like university management, environmental care, university staff, promotion of responsible competencies, graduate employment, and responsib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 62 publications
0
2
0
Order By: Relevance
“…Scholars are calling for more studies investigating the implementation of SR in public entities (Dentchev et al 2018;Kansal et al 2018), especially in the university context (Larrán Jorge et al 2015;Ramos-Monge and Martí-Noguera 2021). How SR should be embedded into the core values and functions of universities' practices at every level is still difficult to understand (Wided 2020) and needs further research.…”
Section: Introductionmentioning
confidence: 99%
“…Scholars are calling for more studies investigating the implementation of SR in public entities (Dentchev et al 2018;Kansal et al 2018), especially in the university context (Larrán Jorge et al 2015;Ramos-Monge and Martí-Noguera 2021). How SR should be embedded into the core values and functions of universities' practices at every level is still difficult to understand (Wided 2020) and needs further research.…”
Section: Introductionmentioning
confidence: 99%
“…Yet, there is an insistent tendency of exploiting SD goals as a representative tool to improve the company’s reputation or to cover-up some shortages and endorse appreciations (Nicolò et al , 2023). In this vein, private institutions are more likely to be engaged within sociocultural activities and USR approaches implementations (Nardo et al , 2021; del Mar Alonso-Almeida et al , 2015) as public ones (Ramos-Monge and Martí-Noguera, 2021; Kappo-Abidemi and Ogujiuba, 2020; Kansal et al , 2018; Dentchev et al , 2018). As well, Amani (2023) has demonstrated that USR influenced the university brand legitimacy with the mediation effect of university brand perceived ethicality in the higher education sector in Tanzania.…”
Section: Research Theoretical Frameworkmentioning
confidence: 99%